Belas Kasihan yang Menggerakkan Pelayanan: Refleksi Eksegetis Matius 9:36 di Era Individualisme - Moranda Girsang; Luciana Haryanto (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to uncover the theological meaning of Jesus' compassion as expressed in Matthew 9:36 through a biblical exegetical approach. This verse demonstrates Jesus' emotional and spiritual response to the plight of the crowd, described as "weary and helpless, like sheep without a shepherd." Using the historical-grammatical exegesis method, this study examines the literary, historical, and linguistic context of the text, particularly the Greek word ἐσπλαγχνίσθη splanchnizomai, which describes compassion born from the depths of the heart. The analysis reveals that Jesus' compassion reflects the core of His messianic mission: God's active involvement in human suffering. This compassion is not merely passive sympathy, but an act that restores, teaches, and shepherds the lost, spiritually and socially. Thus, Matthew 9:36 reveals that Jesus' compassion is the foundation of the Gospel ministry, which emphasizes love, restoration, and God's presence amidst human suffering. Its theological implications emphasize that believers are called to embody Christ's compassion in their lives through loving, empathetic, and caring service to others.